Magnesium sulfate, chorioamnionitis, and neurodevelopment after preterm birth. (3rd June 2015) - Kamyar, M; Manuck, TA; Stoddard, GJ; Varner, MW; Clark, EAS
Abstract : Objective: To assess the neuroprotective effect of magnesium sulfate (MgSO4 ) in preterm children exposed to chorioamnionitis. Design: A secondary analysis of a multicentre randomised controlled trial of antenatal MgSO4 administered to women at risk of preterm birth for the prevention of cerebral palsy (CP). Singleton, non‐anomalous pregnancies with clinical chorioamnionitis, delivering at ≥24 weeks of gestation, were selected. Cases were exposed to antepartum MgSO4 ; controls received placebo. Setting: Multicentre randomised controlled trial. Population: Singleton, non‐anomalous pregnancies with clinical chorioamnionitis, delivering at ≥24 weeks of gestation. Methods: All data were analysed by intention to treat. Univariate and multivariate analyses were performed. Main outcome measures: Primary outcome was a composite of stillbirth, death by the age of 1 year, or moderate or severe CP by the age of 2 years. Secondary outcomes included a composite neonatal outcome as well as neurodevelopmental delay, defined as Bayley II mental and psychomotor developmental indices <70 at the age of 2 years. Subgroup analysis assessed these outcomes in children born at <28 weeks of gestation. Results: A total of 396 children were included, with 192 (48.5%) randomised to MgSO4 . Maternal and delivery characteristics were similar between the groups. The primary outcome occurred in 14.1% of children exposed to MgSO4 and 12.7% of children exposed to placebo (relative risk, RR 1.29; 95% CI 0.70–2.38). Rates of stillbirth, death, moderate–severe CP, and neurodevelopmental delay did not differ between groups. In the subgroup analysis of children born at <28 weeks of gestation, there was no difference in the rates of the primary outcome, nor in the secondary outcomes assessed. [Correction added on 02 March 2016 after online publication: There were errors in statistical data analysis and these have been corrected throughout the article.] Conclusions: Among children at risk for early preterm delivery exposed to chorioamnionitis, antenatal administration of MgSO4 was not associated with improved neurodevelopmental outcome. We do not recommend any change in the guidelines on the administration of MgSO4 for neuroprotection based on this study. Tweetable abstract: MgSO4 was not associated with improved neurodevelopmental outcome in setting of chorioamnionitis. Tweetable abstract: MgSO4 was not associated with improved neurodevelopmental outcome in setting of chorioamnionitis.